Incidence of invasive cervical cancer in the Swiss canton of Vaud, and a note on screening. Issue 2 (June 1989) - Levi, F; La Vecchia, C; Te, V C; Gutzwiller, F
Abstract : Age adjusted incidence rates (World standard) from invasive cervical cancer in the Swiss canton of Vaud decreased from 17.7/100, 000 in 1968-70 to 9.9/100, 000 in 1983-85. The decline was substantial in younger middle age, but no appreciable trend was observed in women over 70. This is consistent with available interview based information on the pattern of cervical screening in the Swiss population. Although there was no organised screening programme in Switzerland, over 80% of women aged 20-44 and 65% of those aged 45-64 reported one or more screening smears over the previous 3 years, compared to only 22% of women aged 65 or over. In the last calendar period, there was an apparent increase in the incidence of invasive cervical cancer (from 2.5 to 6.1/100, 000) in women aged 25-29. Although based on small absolute numbers, this is in agreement with incidence and mortality data from other countries, and may therefore confirm a change in risk factor exposure in younger women.